2021
DOI: 10.1017/s014271642000065x
|View full text |Cite
|
Sign up to set email alerts
|

Parsing preferences and individual differences in nonnative sentence processing: Evidence from eye movements

Abstract: Using both offline and online measures, the present study investigates attachment resolution in relative clauses in English natives (L1) and nonnatives (L2). We test how relative clause resolution interacts with linguistic factors and participant-level individual differences. Previous L1 English studies have demonstrated a low attachment preference and also an “ambiguity advantage” suggesting that L1ers may not have as strong a low attachment preference as is sometimes claimed. We employ a similar design to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Many previous studies have investigated the similarities and differences between L1 and L2 sentence processing. Some previous studies have shown similar sentence processing patterns between L1 and L2 speakers (Cheng et al, 2021;Foote, 2011;Lago & Felser, 2018;Lim & Christianson, 2015;Omaki & Schulz, 2011;Tanner et al, 2012), whereas others have observed different patterns (Felser et al, 2003(Felser et al, , 2009Fujita & Cunnings, 2020;Jiang, 2004;Keating, 2009;Marinis et al, 2005;Papadopoulou & Clahsen, 2003). Some previous studies have reported that interference affects L1 and L2 dependency formation differently.…”
Section: L1 and L2 Differences In Sentence Processingmentioning
confidence: 89%
“…Many previous studies have investigated the similarities and differences between L1 and L2 sentence processing. Some previous studies have shown similar sentence processing patterns between L1 and L2 speakers (Cheng et al, 2021;Foote, 2011;Lago & Felser, 2018;Lim & Christianson, 2015;Omaki & Schulz, 2011;Tanner et al, 2012), whereas others have observed different patterns (Felser et al, 2003(Felser et al, , 2009Fujita & Cunnings, 2020;Jiang, 2004;Keating, 2009;Marinis et al, 2005;Papadopoulou & Clahsen, 2003). Some previous studies have reported that interference affects L1 and L2 dependency formation differently.…”
Section: L1 and L2 Differences In Sentence Processingmentioning
confidence: 89%
“…In an offline task testing ambiguous sentences, Hopp (2014) reported a negative correlation between reading span, tested in the L2, and high attachment in L2 learners of English, with higher L2 span readers preferring low attachment. This finding has recently been replicated by Cheng et al (2021), who found this pattern in both L1 and L2 English readers (with the reading span task again being administered 12 in English). Similar findings have also been reported in some previous L1 studies (e.g.…”
Section: Teasing Apart Capacity-based and Interference-based Approachesmentioning
confidence: 58%
“…Note that as Kim and Christianson only tested ambiguous sentences in their study, and did not compare reading times of ambiguous sentences to those disambiguated to either low or high attachment, as in (3b) and (3c) respectively, this interpretation of their results is difficult to distinguish from one in which participants with higher L1 reading span scores were simply slower, more careful readers overall. Cheng et al (2021) did not report any significant effects of L2 reading span in an eye-tracking study that tested both ambiguous sentences like (3a), and sentences disambiguated to either low or high attachment as in (3b/c) respectively. Hopp (2014) also did not report any significant effects of L2 reading span in an eye-tracking study of L2 readers testing sentences disambiguated to either low or high attachment.…”
Section: Teasing Apart Capacity-based and Interference-based Approachesmentioning
confidence: 83%
“…Another line of work relates individual differences in lexical processing at the participant level to differences in sentence processing. For instance, L2 learners with faster lexical decoding skills demonstrate more target-like processing of ambiguous sentences, while less efficient lexical decoders are not sensitive to L1-L2 structural differences in sentence processing (Cheng et al, 2021;Hopp, 2014). Such findings extend to the processing of grammatical gender (Hopp, 2013), suggesting that efficient lexical access is a prerequisite for target grammatical processing.…”
Section: Interactions Between Lexical and Syntactic Processingmentioning
confidence: 94%